Experiences of accreditation impact in general practice – a qualitative study among general practitioners and their staff - Kousgaard, Marius Brostrøm (BMC Fam Pract, 2019)
BACKGROUND: Accreditation is a widespread tool for quality management in health care. However, there is lack of research on the impact of accreditation, particularly in general practice. This study explores how general practitioners and their staff experienced the impact of a mandatory accreditation program in Denmark. METHODS: Qualitative interviews with general practitioners and staff from 11 clinics. The respondents were interviewed twice: during preparation and after the survey visit. The interviews were analyzed using thematic analysis, and all specific changes and other types of impact were extracted from the transcribed interview data from each clinic. RESULTS: The impact of accreditation varied markedly among the clinics as did the participants’ overall assessments of accreditation. Concerning specific changes in behavior and physical infrastructure, some clinics had only implemented a few minor changes in response to accreditation, some had made a relatively moderate number of changes, and a few clinics had made relatively many changes including a few pronounced ones. Further, some participants experienced that accreditation had enhanced knowledge sharing or upgraded competencies, and increased job satisfaction. However, the workload related to accreditation was emphasized as a problem by a majority of the professionals and for a few, accreditation had influenced job satisfaction negatively. CONCLUSION: Accreditation may affect general practice clinics in very different ways. In spite of several examples of positive impact, the results suggest that it is difficult to design a mandatory accreditation program for general practice in which most professionals experience that the benefits of accreditation equal the resources used in the process.